1990
DOI: 10.1017/s0022215100113477
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis as an unusual presentation of an antrochoanal polyp

Abstract: Antrochoanal polyps rarely present with severe epistaxis. We present the case of a young male patient who presented in such a manner, thus leading to the suspicion of an angiofibroma as the underlying pathology. The radiological investigations, treatment and pathological features are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 3 publications
(2 reference statements)
3
15
0
1
Order By: Relevance
“…The majority of patients are younger than 40 years [1,3,4,6,7]. Unilateral nasal obstruction is the most common presenting symptom [1,5,7,9,10]. Epistaxis is a rare feature of this condition [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of patients are younger than 40 years [1,3,4,6,7]. Unilateral nasal obstruction is the most common presenting symptom [1,5,7,9,10]. Epistaxis is a rare feature of this condition [9].…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral nasal obstruction is the most common presenting symptom [1,5,7,9,10]. Epistaxis is a rare feature of this condition [9]. Sphenochoanal polyps may present with headaches, due to blockage of the sphenoid sinus [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Other clinical manifestations are rhinorrhoea, bleeding, snoring, foreign body sensation, halitosis, headache, post nasal drip and loss of sense of smell. There are occasional reports of cases starting with epistaxis 19 , polyp strangulation 20 , spontaneous amputation 21 , dyspnoea and dysphagia 22 , with extension to the mouth producing dysphagia, speech disorders and obstructive sleep apnoea 23 . In our case, the presentation was similar to that of antrochoanal polyp.…”
Section: Discussionmentioning
confidence: 99%
“…According to Marshal and Gomes et al 3 , depending on its size, the antrochoanal polyp may cause Eustachian tube obstruction and thus, unilateral secretory otitis media, which did not happen in the present series. Robson et al 10 described the case of a young man with severe epistaxis as the main symptom. In the present study, we found 6 (37.5%) patients with epistaxis, and none of them with severe nasal bleeding.…”
mentioning
confidence: 99%